Case of hidden tooth: mesiodens fortuitously discovered on a cone-beam CT examination. Issue 4 (21st April 2022) - Perez, Alexandre; Stergiopulos, Ourania; Lenoir, Vincent; Lombardi, Tommaso
Abstract : Mesiodens is the most common type of supernumerary tooth, located between the maxillary central incisors. A young man was referred by his orthodontist for management of a supernumerary tooth located in quadrant I, superposed to the bottom of the right maxillary sinus, distally orientated with the crown in contact with the apex of the palatal root of the maxillary first molar. The tooth was found on a panoramic radiography before starting his orthodontic treatment. To remove it and in order to study, its relationship to the anatomical structures a cone-beam CT examination was performed. This revealed the presence of a mesiodens located on the right paramedian maxillary area. Pericoronal tissue submitted for histopathological examination showed an uninflamed dental follicle. Healing was uneventful. This case shows that mesiodens outside the arch, located in the posterior palate, may be not discovered in a panoramic radiograph.